P–111 Development of a flow cytometric assay for membrane lipid oxidation in human sperm. (6th August 2021) - Bosman, L; Ellis, P; Homa, S; Griffin, D
Abstract: Study question: Is a commercially available lipid peroxidation assay sensitive enough to detect sperm lipid membrane damage and thus provide a novel indicator of male fertility status? Summary answer: Provisional results demonstrate the novelty of creating a protocol to identify and quantify sperm lipid membrane damage and indicate possible insight into individual male fertility. What is known already: Cytotoxic lipid aldehydes such as 4-hydroxynonenal (4HNE) created by the damaging effects of reactive oxygen species (ROS) have been studied extensively in sperm, as an indicator of male fertility. This is due to their connection with detrimental effects on sperm function such as morphology, acrosome reactions, motility and fertilization of the oocyte. Although literature states the mechanisms of damage caused to the lipid membrane of the sperm cell, there is no evidence of its quantification or usage as a commercial fertility indicator for human males. Study design, size, duration: Since the assay is still being developed, there is no formal study size or duration. The goal of this pilot study is to determine whether a commercial lipid peroxidation assay can detect the difference between sperm with high levels of oxidative damage and control sperm cells. We used the remains of sperm samples initially collected for standard semen analysis, which were flash-frozen and then assayed with / without hydrogen peroxide treatment to induce oxidative damage. Participants/materials, setting, methods: Frozen sperm from consenting donors (n = 21) were washed, optionally treated with hydrogen peroxide to induce oxidative damage, stained with a commercially available lipid peroxidation sensor (LPS, Abcam ab243377), and the resulting fluorescence quantitated by flow cytometry. Assay optimization varied the numbers of sperm input to the protocol, the concentration of the peroxidation sensor, the amount and duration of hydrogen peroxide treatment and the effect of paraformaldehyde (PFA) fixation of samples before or after staining. Main results and the role of chance: Successful detection of lipid damage in control samples We observed a significant difference at a p-value < 0.05 between untreated samples and all positive controls with hydrogen peroxide concentrations stronger than 500uM (p < 0.038) . This indicates that we can detect sperm bearing oxidative damage, and establishes the conditions required to make a positive control sample. Establishment of assay parameters Results indicate the concentration of sperm input to the protocol is not a significant factor for concentrations below 5 million/ml. Low concentration samples thus do not require further dilution before testing. Correlation with DNA damage A significant direct strong positive Pearson correlation coefficient (R = 0.93, p < 0.023) was found between samples with low DNA fragmentation index (DFI (%), measured by flow cytometric staining with acridine orange) and the LPS flow cytometric data (%). Limitations, reasons for caution: As yet our data only addresses high level lipid damage induced by peroxide treatment. It remains to be established whether it is possible to detect endogenous LPO damage due to oxidative stress in semen. Future work will correlate our data with motility information and oxidative stress data (measured by MiOXSYS). Wider implications of the findings: If we are able to develop a direct assay for sperm LPO, this will allow an additional avenue for testing patients with unexplained male infertility, which could in turn affect treatment choices and ART methodology. Improved diagnosis and treatment will potentially improve the lives of families with their fertility matters. Trial registration number: Not applicable